Dialectic Perspective on Interpersonal Conflict of Pre-Divorce and Its Reconciliation - Patrissia, Ressa Uli; Jamalullail (Mediator: Jurnal Komunikasi, 2024)
This research examines the Dialectic Perspective of Interpersonal Conflict of Pre-Divorce and Its Reconciliation. The development of the divorce rate in Indonesia has reached its peak in 2022 compared to the last six years. These phenomena interest the researcher in discovering how the married couple in dispute can resolve their marriage and repair their relationship. This research is based on the theory of relational dialectics as a ground theory, supported by narrative sense-making as the middle theory, and complemented by dialogic listening theory as the applied theory for supporting conflict resolution. The method used was a qualitative descriptive approach to study the case of four informants with criteria determined by the researcher. The results of this study indicate a framework dimension from the precursor of marriage conflict, namely individual character and family character, forward to the process of the conflict where the dimension of interpersonal conflict and addressing or problem-solving of the conflict is found, to the reconciliation dimension that contributes to the success of reconciliation such as time, agreement, use of future narrative, satisfaction, financial performance, habitual interdependence, and religion and cultural constraints.